Huge areas of diverse tropical forest are lost or degraded every year with dramatic consequences for biodiversity. Human activities such as deforestation, fragmentation, over-exploitation, and monoculture practices are the main drivers of tropical forest biodiversity loss. Investigating of these threats with focusses on changes in species richness or species diversity will be able to minimize any impact of human activities at the early stage in a certain region. Therefore, to know the impact of - HARI SUTRISNO (Bogor Agricultural University, Indonesia, 2010)
Huge areas of diverse tropical forest are lost or degraded every year with dramatic consequences for biodiversity. Human activities such as deforestation, fragmentation, over-exploitation, and monoculture practices are the main drivers of tropical forest biodiversity loss. Investigating of these threats with focusses on changes in species richness or species diversity will be able to minimize any impact of human activities at the early stage in a certain region. Therefore, to know the impact of human activities to dynamic of insect communities in Gunung Salak, West Java, we measured moth diversity and their structure within communities by comparing the index diversity, species richness and species composition across five different habitat types. The results showed that the habitat changes due to human activities had changed not only to the moth diversity but also to their structure within communities. The number of moth species decreased significantly as well as the number of lower taxa (family) in the disturbed forest (secondary forest, Agathis forest, and transition area) within ranges: 20-50 and 10-20%. The composition of the two main families, Geometridae and Noctuidae also showed a major change, family Geometridae decreased within ranges 10-50% in the disturbed area but Noctuidae increased up to 50% in those areas. Indeed, habitat lost due to human activities such as illegal logging, change of land use and land clearing is the main threats to decrease on macro-moth diversity and change their structures within communities.